Designing Clinical Trials for the Treatment of Membranous Nephropathy in the Anti-Phospholipase A2 Receptor 1 Era: Results of a NephCure Membranous Nephropathy Workshop - Marco Prunotto; Patrick H. Nachman; Barbara S. Gillespie; Laurence H. Beck; Aliza M. Thompson; Austin H. Hu; Elizabeth A. Stafford; Josh M. Tarnoff; Brad H. Rovin (Glomerular Diseases)
Primary membranous nephropathy is a common cause of adult-onset nephrotic syndrome, with an overall incidence of 12 cases per million per year. Primary membranous nephropathy is an autoimmune kidney disease; however, primary membranous nephropathy autoantigens remained elusive until 2009, when the M-type phospholipase A2 receptor 1 (PLA2R) was identified as a disease autoantigen. This was followed relatively rapidly by the identification of several other autoantigens. Autoantibodies against PLA2R are detectable in ≈75% of patients with primary membranous nephropathy. The discovery of circulating and deposited autoantibodies against PLA2R offers an opportunity in nephrology to personalize disease management. On January 14, 2023, NephCure Kidney International convened a scientific workshop in Arlington, Virginia, to discuss the state of the science on autoantibodies against PLA2R and considerations related to the incorporation of autoantibodies against PLA2R in drug development programs for membranous nephropathy. The present report captures the discussion that occurred at the Membranous Nephropathy Scientific Workshop. Primary membranous nephropathy is a common cause of adult-onset nephrotic syndrome, with an overall incidence of 12 cases per million per year. Primary membranous nephropathy is an autoimmune kidney disease; however, primary membranous nephropathy autoantigens remained elusive until 2009, when the M-type phospholipase A2 receptor 1 (PLA2R) was identified as a disease autoantigen. This was followed relatively rapidly by the identification of several other autoantigens. Autoantibodies against PLA2R are detectable in ≈75% of patients with primary membranous nephropathy. The discovery of circulating and deposited autoantibodies against PLA2R offers an opportunity in nephrology to personalize disease management. On January 14, 2023, NephCure Kidney International convened a scientific workshop in Arlington, Virginia, to discuss the state of the science on autoantibodies against PLA2R and considerations related to the incorporation of autoantibodies against PLA2R in drug development programs for membranous nephropathy. The present report captures the discussion that occurred at the Membranous Nephropathy Scientific Workshop.